2017
DOI: 10.1177/1708538117706273
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis after carotid artery stenting

Abstract: As a common etiology for ischemic stroke, atherosclerotic carotid stenosis has been targeted by vascular surgery since 1950s. Compared with carotid endarterectomy, carotid angioplasty and stenting (CAS) is almost similarly efficacious and less invasive. These advantages make CAS an alternative in treating carotid stenosis. However, accumulative evidences suggested that the long-term benefit-risk ratio of CAS may be decreased or even neutralized by the complications related to in-stent restenosis (ISR). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 108 publications
(133 reference statements)
0
29
0
Order By: Relevance
“…This might be related to the variations among the studies regarding the definition of restenosis and the modalities used to assess the degree of restenosis and its definition, especially the estimated degree of stenosis and the corresponding PSV in DUS as was suggested. [ 8 ] The discordant findings might also have been affected by the limited number of samples in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…This might be related to the variations among the studies regarding the definition of restenosis and the modalities used to assess the degree of restenosis and its definition, especially the estimated degree of stenosis and the corresponding PSV in DUS as was suggested. [ 8 ] The discordant findings might also have been affected by the limited number of samples in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…Knowledge of the predictors of recurrent stenosis is an important criterion for determining postoperative follow-up intervals. Several studies revealed primarily diabetes, with its high potential for neointimal proliferation, as well as hyperlipidemia, female sex, nicotine abuse, and a plaque length of over 2 cm [4,5,[10][11][12][13] as predictors for in-stent recurrent stenosis, but not plaque morphology as determined preoperatively by ultrasound (gray scale median analysis), plaque echogenicity [14,15], or plaque calcification [16]. The causes of hemodynamically relevant recurrent stenosis primarily include the onset of in-stent neointimal proliferation usually within the first year, as well as atherosclerosis that progresses in the further course with in-stent stenosis due to plaque.…”
Section: Predictors Of Recurrencementioning
confidence: 99%
“…however, put in-stent recurrent stenosis at between 1% and 50% [1][2][3][4][5]. This variation is due to a number of different factors: 4 Definition of recurrent stenosis (degree of stenosis) 4 Patient collective composition 4 Duration of follow-up and stent design 4 Prevalence of predictors for recurrent stenosis in the patient collective 4 Measurement methods (peak systolic velocity, PSV, in duplex ultrasound) to grade stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent stenosis is a known risk factor of ipsilateral stroke, 4-7 and the collective incidence of ISR varies from 1.6% to 24%. [8][9][10] Several factors have been associated with restenosis after CAS, including advanced age, female sex, dyslipidemia, diabetes and the characteristics of the original plaques. [11][12][13][14][15][16] ISR is mainly attributed to neointimal hyperplasia (NIH) in the early stage after the procedure.…”
mentioning
confidence: 99%